Chest pain in children: an update - Hussain, MZ; Ishrat, S; Salehuddin, M; Mahmood, M; Islam, MT (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):165-170 The abstract of this article is available on the PubMed website